A critical mini-review on the low-field nuclear magnetic resonance investigation of pore coupling effects in near-surface environments - Soto Bravo, Francisca; Zhang, Chi (Frontiers in Water, 2023)
The assessment and monitoring of groundwater resources is of increasing importance to ensure the continuous supply of fresh water for human activity and endangered ecosystems. These groundwater resources include fully saturated aquifers, water in unsaturated soil, and water trapped as rock moisture in weathered bedrocks. Low-field nuclear magnetic resonance (NMR) is a method with unique sensitivity to pore water, as it is based on the magnetization and relaxation behaviour of the spin magnetic moment of hydrogen atoms forming water molecules. It is a cost-effective and minimally-invasive technology that can help characterise the pore structures and the groundwater distribution and transport in different type of subsurface materials. However, the interpretation of NMR data from samples with complex bimodal or multimodal porous geometries requires the consideration of pore coupling effects. A pore-coupled system presents significant magnetization exchange between macro- and micropores within the measurement time, making the independent characterization of each pore environment difficult. Developing a better understanding of pore coupling is of great importance for the accurate estimation of hydrogeological parameters from NMR data. This mini-review presents the state-of-art in research exploring the two factors controlling pore coupling: surface geochemistry and network connectivity, summarizes existing experimental and numerical modeling approaches that have been used to study pore coupling and discusses the pore coupling effects in fully and partially saturated conditions. At the end of this review, we outline major knowledge gaps and highlight the research needs in the vadose zone.